Evolutionary conserved regulation of HIF-1β by NF-κB. - Patrick van Uden; Niall S Kenneth; Ryan Webster; H Arno Müller; Sharon Mudie; Sonia Rocha (PLoS Genetics)
Hypoxia Inducible Factor-1 (HIF-1) is essential for mammalian development and is the principal transcription factor activated by low oxygen tensions. HIF-α subunit quantities and their associated activity are regulated in a post-translational manner, through the concerted action of a class of enzymes called Prolyl Hydroxylases (PHDs) and Factor Inhibiting HIF (FIH) respectively. However, alternative modes of HIF-α regulation such as translation or transcription are under-investigated, and their importance has not been firmly established. Here, we demonstrate that NF-κB regulates the HIF pathway in a significant and evolutionary conserved manner. We demonstrate that NF-κB directly regulates HIF-1β mRNA and protein. In addition, we found that NF-κB-mediated changes in HIF-1β result in modulation of HIF-2α protein. HIF-1β overexpression can rescue HIF-2α protein levels following NF-κB depletion. Significantly, NF-κB regulates HIF-1β (tango) and HIF-α (sima) levels and activity (Hph/fatiga, ImpL3/ldha) in Drosophila, both in normoxia and hypoxia, indicating an evolutionary conserved mode of regulation. These results reveal a novel mechanism of HIF regulation, with impact in the development of novel therapeutic strategies for HIF-related pathologies including ageing, ischemia, and cancer.